2010
DOI: 10.1111/j.1365-3156.2009.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

National health insurance coverage and socio‐economic status in a rural district of Ghana

Abstract: Summaryobjective To explore the association between socio-economic status (SES) and health insurance subscription to the Ghanaian National Health Insurance Scheme (NHIS) of residents of the Asante Akim North district of the Ashanti Region, Ghana.methods In the course of a community survey, data on asset variables (e.g. electricity, housing conditions and other variables) and on NHIS subscription were collected on the household level in 99 villages. Using principal components analysis, households were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
92
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 26 publications
12
92
1
Order By: Relevance
“…Similarly, a graduated, means-tested premium has been abandoned in favor of a low, fixed annual premium for all (the equivalent of about US$7 per year) due to difficulties in collection (Witter and Garshong 2009). While affiliation in Ghana has been growing rapidly, only an estimated 59 percent of the population has registered with the national health insurance service, and evidence shows that enrollment unequally favors the relatively wealthy (Asante and Aikins 2008;Sarpong et al 2010). Budget shortfalls resulted in a failure to pay outstanding facility claims in 2008, which severely undermined the legitimacy of the program in the eyes of providers (Witter and Garshong 2009).…”
Section: Fourth Implementation: Things Fall Apartmentioning
confidence: 96%
“…Similarly, a graduated, means-tested premium has been abandoned in favor of a low, fixed annual premium for all (the equivalent of about US$7 per year) due to difficulties in collection (Witter and Garshong 2009). While affiliation in Ghana has been growing rapidly, only an estimated 59 percent of the population has registered with the national health insurance service, and evidence shows that enrollment unequally favors the relatively wealthy (Asante and Aikins 2008;Sarpong et al 2010). Budget shortfalls resulted in a failure to pay outstanding facility claims in 2008, which severely undermined the legitimacy of the program in the eyes of providers (Witter and Garshong 2009).…”
Section: Fourth Implementation: Things Fall Apartmentioning
confidence: 96%
“…It has been found that certain groups of persons, especially the poor are systematically excluded from the NHIS [11][12][13][14]. Women have been noted to face greater difficulties in accessing adequate care.…”
Section: Introductionmentioning
confidence: 99%
“…Health insurance replaces outof-pocket expenditures at the point of need with smaller regular contribution (premiums), which allows individuals to gain access to care, especially some of those who previously could not afford it [20][21]. While health insurance improves access to health care for members, there will still be individuals who cannot afford the premiums [13,22]. Access to health care can also be restricted by other indirect financial and non-financial barriers, such as travel costs, loss of income, and other social and cultural values [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…3 (p. 3) After declaring independence from British rule in 1957, healthcare was available without point of service fee. 4 (p. 128) This changed to a cash and carry system in the 1980s, 5 creating access obstacles. 4 President Kufuor (elected 2001 and 2005), 6 attempted to provide national healthcare for all and The National Health Insurance Law passed in 2003.…”
Section: Introductionmentioning
confidence: 99%